Climate Change Vulnerability Assessment. A Framework for Urban Planning Practitioners in Ilala District, Dar es Salaam City, Tanzania. - NYASHILU, Issa Musa; KIUNSI, Robert Benjamin; KYESSI, Alphoce Gabriel (International Journal of Environmental, Sustainability, and Social Science, 2024)
Global climate change is a challenge undisputable in the intervening time. The Global South countries are the most vulnerable to global climate change. It is indicated by the prevalence of climate hazards including extreme temperatures leading to urban heat island effects(UHI, prolonged droughts, melting of ice caps, increased extreme weather events such as tropical cyclones, heat waves, urban flooding, sea level rise, and coastal erosion resulting in salty water intrusion into freshwater aquifers. This paper explores a framework for climate change vulnerability assessment in the urban planning process in cities of the Global South. A sample of 95 households was selected purposely for study. Data collection methods involved interviews by structured questionnaires, surveys, focused group discussions, observations, and documentary reviews. Quantitative data analysis was done using a statistical package for social sciences. Qualitative data were analysed by content analysis, narrative analysis, and interpretive phenomenological analysis. Results showed that climate change physical infrastructures, socioeconomic activities and livelihoods and ecosystems were vulnerable to climate change-induced flooding in urban areas. The study concludes that adoption of new urban planning process enhances resilience and sustainable cities and communities in cities of the Global South.